Using High-Dimensional Approaches to Probe Monocytes and Macrophages in Cardiovascular Disease - Dick, Sarah A.; Zaman, Rysa; Epelman, Slava (Frontiers in Immunology, 2019)
High dimensional approaches that characterize single cells at unprecedented depth have helped uncover unappreciated heterogeneity, a better understanding of myeloid cell origins, developmental relationships and functions. These advancements are particularly important in cardiovascular disease, which remains the leading cause of death worldwide. Chronic processes, such as the development of atherosclerotic plaques, are generated by the gradual, monocyte-dependent inflammatory response within the vessel, contrasts with the acute response within the myocardium that occurs when a vessel is occluded. Monocytes and macrophages differentially contribute to tissue injury, repair and regeneration in these contexts, yet many questions remain about which myeloid cell types are involved in a coordinated, organ-level sterile inflammatory response. Single cell RNA sequencing, combined with functional techniques, have demonstrated that at least three populations of resident cardiac macrophages exist, and after tissue injury, there is significant diversification of the tissue macrophage pool driven by recruited monocytes. While these studies have provided important insights, they raise many new questions and avenues for future exploration. For example, how transcriptional defined sub-populations of cardiac macrophages relate to each other. Are they different states along a predefined program of macrophage differentiation or do local microenvironments drive a newly recruited monocytes into distinct functions? The answers to these questions will require incorporating high-dimensional approaches into biologically relevant in vivo experimental systems to ensure the predicted heterogeneity possess a functional outcome.